414. Association of SARS-CoV-2 Genomic Load Trends with Clinical Status in COVID-19:A Retrospective Analysis from an Academic Hospital Center in New York City. (31st December 2020) - Zacharioudakis, Ioannis; Zervou, Fainareti; Prasad, Prithiv; Shao, Yongzhao; Basu, Atreyee; Inglima, Kenneth; Weisenberg, Scott; Aguero-Rosenfeld, Maria E
Abstract: Background: The Infectious Diseases Society of America has identified the potential use of SARS-CoV-2 genomic load for prognostication purposes as a key research question. Methods: We designed a retrospective cohort study that included adult patients with COVID-19 pneumonia who had at least 2 positive nasopharyngeal tests at least 24 hours apart to study the correlation between the change in the genomic load of SARS-CoV-2 in nasopharyngeal samples, as reflected by the Cycle threshold (Ct) value of the real-time Polymerase Chain Reaction (PCR) assay, with change in clinical status. The Sequential Organ Failure Assessment (SOFA) score was used as a surrogate for patients' clinical status. A linear mixed-effects regression analysis was performed. Results: Among 457 patients who presented to the emergency department between 3/31/2020- 4/10/2020, we identified 42 patients who met the inclusion criteria. The median initial SOFA score was 2 (IQR 2–3). 20 out of 42 patients had a lower SOFA score on their subsequent tests. We identified a statistically significant inverse correlation between the change in SOFA score and change in the Ct value with a decrease in SOFA score by 0.05 (SE 0.02; p < 0.05) for an increase in Ct values by 1. This correlation was independent of the duration of symptoms. Flow chart A graph of the Cycle Threshold (Ct) values of the of Cepheid Xpert® Xpress SARS-CoV-2 assay measured on repeat screening of the 42 included patients. Graph of the fitted SOFA scores based on the Cycle Threshold values per patient. Conclusion: Our findings suggest that an increasing Ct value in sequential tests may be of prognostic value for patients diagnosed with COVID-19 pneumonia. Before repeat testing can be recommended routinely in clinical practice as a predictor of disease outcomes, prospective studies with a standardized interval between repeat tests should confirm our findings. Disclosures: All Authors : No reported disclosures